Biochemical and fatty acid composition of Arca noae (Bivalvia: Arcidae) from the Mali Ston Bay, Adriatic Sea - DUPCIC RADIC, I.; CARIĆ, M.; NAJDEK, M.; JASPRICA, N.; BOLOTIN, J.; PEHARDA, M.; BRATOŠ CETINIĆ, A. (Mediterranean Marine Science, 2014)
Biochemical and fatty acid composition of the bivalve Arca noae were investigated in the Mali Ston Bay in relation to environmental conditions. Sampling was carried out monthly, from December 2001 to November 2002. Wet shellfish meat consists on average of 77.61% water and 22.39% dry matter, while dry shellfish meat consists on average of 89.04% organic and 10.96% inorganic matter. PCA analysis identified temperature, nitrate, silicate, MICRO, Chl a and salinity as the most important environmental factors influencing biochemical composition of A. noae. An increase of dry weight content of A. noae was observed during the spring when both the sea temperature and food supply increased rapidly. Contents of protein (54.39-62.06% of dry weight), carbohydrate (4.13-8.07% of dry weight) and lipid (3.46-8.58% of dry weight) varied significantly during the year. Protein and lipid level reached the maximum value in June. The fatty acid profiles of total lipids extracted from A. noae showed high level of unsaturation (UNS/SAT 1.9-3.4). Total polyunsaturated fatty acids (PUFA) represented the majority of total fatty acids (40.3-59.9% of total fatty acids) and the most abundant were eicosapentaenoic (20:5n-3) and docosahexaenoic (22:6n-3) acid. n-3/n-6 PUFA ratio value varied between 2.1 and 5.0 and was the highest during the spring (April to June). Due to their low lipid and high percentages of healthy polyunsaturated fatty acids A. noae can be evaluated as a quality seafood product. The most suitable period of the year for its consumption is in the spring when it reaches its highest nutritional values.